Tracking Chromatid Segregation to Identify Human Cardiac Stem Cells that Regenerate Extensively the Infarcted Myocardium - Kajstura, Jan (2012)
RATIONALE: According to the immortal DNA strand hypothesis, dividing stem cells selectively segregate chromosomes carrying the old template DNA, opposing accumulation of mutations resulting from non-repaired replication errors and attenuating telomere shortening. OBJECTIVE: Based on the premise of the immortal DNA strand hypothesis, we propose that stem cells retaining the old DNA would represent the most powerful cells for myocardial regeneration. METHODS AND RESULTS: Division of hCSCs by non-random and random segregation of chromatids was documented by clonal assay of bromodeoxyuridine-tagged hCSCs. Additionally, their growth properties were determined by a series of in vitro and in vivo studies. We report that a small class of hCSCs retain during replication the mother DNA and generate two daughter cells, which carry the old and new DNA, respectively. hCSCs with immortal DNA form a pool of non-senescent cells with longer telomeres and higher proliferative capacity. The self-renewal and long-term repopulating ability of these cells was shown in serial-transplantation assays in the infarcted heart; these cells created a chimeric organ, composed of spared rat and regenerated human cardiomyocytes and coronary vessels, leading to a remarkable restoration of cardiac structure and function. The documentation that hCSCs divide by asymmetric and symmetric chromatid segregation supports the view that the human heart is a self-renewing organ regulated by a compartment of resident hCSCs. CONCLUSIONS: The impressive recovery in ventricular hemodynamics and anatomy mediated by clonal hCSCs carrying the “mother” DNA underscores the clinical relevance of this stem cell class for the management of heart failure in humans.